Optimization of without SCM concrete exposed to seawater according to minimum cost and CO2 emissions: Sustainable design with ABC algorithm - Kaplan, Gökhan; Bayraktar, Oguzhan Yavuz; Bayraktar, Tugrul (Elsevier BV, 2023)
© 2023 Elsevier LtdThe service life of marine concrete structures is relatively shorter due to various salts in seawater. In this context, assistance is obtained from the exposure classes in standards such as EN 206. In this study, an ABC-based (artificial bee colony) algorithm was developed that considers the CO2 emissions and cost analysis of concrete designed according to EN 206 standards. The number of studies involving algorithms in designs according to regulations and standards is very few in the literature. In addition, Supplementary Cementitious Materials (SCMs) are generally used in concretes exposed to sea water. This study investigated the physical, mechanical, durability, microstructure, cost and sustainability properties of concretes without SCM. This study produced nine concrete mixes with different cement dosages (260–300–340 kg/m3) and a water/cement ratio (0.45,0.55, and 0.65). The mixes were cured in normal water (NWC) and seawater (SWC). As the cement mixes’ cement dosage increased, the water absorption and apparent porosity values decreased. Since the increase in the w/c ratio increased the capillary void content of the mixes, it enhanced the porosity and sorptivity values. While the 28d compressive strength of NWC-applied concretes varies between 31.3 and 39.8 MPa, the compressive strength of SWC-applied concrete varies between 30.7 and 36.8 MPa. After 80 wetting-drying cycles, the compressive strength of the concretes decreased below 20 MPa. The CO2 emission values of the concrete vary between 270 and 343 kg and their costs range between 17.9 and 21.5 $/m3. According to the ABC algorithm, it was determined that cement dosage should be 260 kg/m3, w/c ratio should be 0.45 for high compressive strength, low cost, and CO2 emission. As a result, it has been determined that a lower cost and more durable concrete design can be made if methods such as the ABC algorithm are combined with EN 206 standards.